STRATEGY OF MANAGEMENT HUMAN RESOURCES AND OPPORTUNITIES IN THE DIGITAL ERA IN IMPROVING CAREER DEVELOPMENT (A Case Study of Generation Z in Rangkasbitung Subdistrict) - Maslah; Indah Lestari; Andri Susilo (The Asia Pacific Journal Of Management Studies, 2024)
This study aims to analyze the strategies and opportunities of human resource management in the digital era to improve the career development of Generation Z in Rangkasbitung Subdistrict. The digital era has changed the way Generation Z views and manages their careers, especially in utilizing the growing digital technology. This research used a qualitative approach with a case study method, where data was collected through in-depth interviews with several informants from Generation Z who work in various fields. The results show that digital technology supports daily work, especially in communication, task management, and learning. In addition, human resource management strategies such as training, mentoring, and regular performance evaluations have proven effective in improving Generation Z's competencies and readiness to face future career challenges. Despite facing challenges such as adaptation to new technologies and undisciplined student management, the opportunities offered by the digital era, such as easy access to learning resources and the chance to upgrade skills through online courses, are key drivers in their career development. This study concludes that proper support from the work environment, supported by an adaptive and flexible human resource management strategy, can help Generation Z in Rangkasbitung Sub-district to continue to develop and adapt in their careers in the digital era. Keywords: Human Resource Management, Opportunities in Digital Era, Career Development, Generation Z.